A Wearable Activity Tracker Intervention With and Without Weekly Behavioral Support Emails to Promote Physical Activity Among Women Who Are Overweight or Obese: Randomized Controlled Trial - Melissa Black; Jennifer Brunet (JMIR Publications, 2021)
BackgroundPhysical activity (PA) plays a fundamental role in combating the current obesity epidemic; however, most women who are overweight or obese are generally physically inactive. Wearable activity tracker interventions can help increase the PA levels in this population. Supplementing such interventions with behavioral support emails may further improve their effectiveness, but this remains to be confirmed. ObjectiveThis study aims to determine if adding behavioral support emails to a wearable activity tracker intervention can further increase PA levels among women who are overweight or obese in comparison to a wearable activity tracker-only intervention and a control condition. MethodsWomen with a BMI ≥25 kg/m2 who were not meeting the Canadian PA guidelines for aerobic and strength training were randomized into 1 of 3 groups. Group 1 received 6 weekly behavioral support emails, a wearable activity tracker, and a copy of the Canadian PA guidelines. Group 2 received a wearable activity tracker and a copy of the Canadian PA guidelines, and group 3 (control condition) received a copy of the Canadian PA guidelines. Self-reported data for walking and moderate to vigorous intensity PA were collected preintervention (week 0; prerandomization), postintervention (7 weeks postrandomization), and at follow-up (21 weeks postrandomization) and analyzed as metabolic equivalent of task minutes per week. In addition, potential mechanisms of behavior change (ie, basic psychological needs satisfaction and motivational regulations) were assessed for within- and between-group differences at all 3 time points. Data were analyzed using nonparametric statistical tests. ResultsA total of 49 women were recruited; data from 47 women (mean age 37.57 years, SD 11.78 years; mean BMI 31.69 kg/m2, SD 5.97 kg/m2) were available for analysis. Group 1 reported a significant increase in walking from preintervention to postintervention (χ22=7.5; P=.02) but not in moderate to vigorous intensity PA (P=.24). Group 1 also reported significant increases in perceptions of competence from preintervention to follow-up (χ22=7.6; P=.02) and relatedness from preintervention to follow-up (χ22=8.7; P=.005). Increases in perceived autonomy were observed for group 2 (χ22=7.0) and group 3 (χ22=10.6). There were no significant changes in the motivational regulations within the groups. The difference between the groups was not significant for any outcome variable. ConclusionsThe results suggest that adding behavioral support emails to a wearable activity tracker intervention may help to increase time spent walking and perceptions of competence and relatedness for PA among women who are overweight or obese. Trial RegistrationClinicalTrials.gov NCT03601663; http://clinicaltrials.gov/ct2/show/NCT03601663